ANALYSIS OF CONCRETE AND REINFORCEMENT QUANTITY TAKE-OFF OF BRIDGE APPROACH STRUCTURES USING AUTODESK REVIT 2024 AND CONVENTIONAL METHODS - Rubiasih Afrida; Dedi Enda (RADJA PUBLIKA, 2026)
The development of Building Information Modeling (BIM) has accelerated the digitalization of construction planning and management processes, including Quantity Take Off (QTO) calculations that require high speed and accuracy. However, the estimation of concrete and reinforcement quantities for bridge approach structures is still commonly performed using conventional methods, which are prone to calculation errors and require relatively more time. In addition, studies investigating the application of BIM to bridge approach structures with curved geometries remain limited. This study aims to analyze and compare the Quantity Take Off results of concrete and reinforcement obtained using Autodesk Revit 2024 and conventional methods for the bridge approach structures of Sei Kuala and Sei Akar Bridges on the Bagan Jaya–Tembilahan road section. A comparative quantitative research method was employed by developing a three-dimensional model based on project design data and extracting quantity information using the Schedule/Quantity feature in Autodesk Revit 2024. The accuracy of the calculated quantities was evaluated using the Average Error and Root Mean Square Error (RMSE) parameters. The results indicate that Autodesk Revit 2024 is capable of producing quantity estimates that closely correspond to those obtained through conventional methods, with an Average Error of 2.619% for concrete and 5.920% for reinforcement, and RMSE values of 0.473 m³ and 0.656 m³, respectively. The largest deviation was observed in the deck slab reinforcement due to the curved geometry of the bridge approach, which caused Autodesk Revit to calculate the length of each reinforcing bar individually. Overall, the findings demonstrate that Autodesk Revit 2024 can serve as an effective and reliable alternative for performing Quantity Take Off on bridge approach structures with complex geometries.